Conditions and possibilities for public policies evaluation in Argentina from a integrated perspective - Brissón, María Eugenia; Mattalini, Matías; Neirotti, Nerio (Revista Aval, 2020)
In this article we propose to present the main findings of a research whose objective has been to inquire about the conditions of possibility for an integrated public policy evaluation system to be configured in Argentina. We built from previous research in which we delve into the institutionalization of evaluation in the National Public Administration. We update norms, structures, devices and reports from official platforms, web pages and search engines. The challenge of building a new evaluation paradigm that emerges in response to the demands imposed by a model of State and society based on well-being and the realization of the rights of the population support the analysis. We present a description of existing institutional conditions for evaluation identifying continuities and ruptures between two periods of different governments: 2011-2015 and 2016-2019.